Solid Waste Pollution and its Impact on the Road Network in the Green Mountain Region: A Study in Environmental Geography (Al-Farooq Journal of Sciences, 2026)
The road network in the study area suffers from the spread of random solid waste dumps, and this problem is exacerbated day by day and steadily as a result of the lack of environmental awareness among citizens and lack of hygiene as well as the economic conditions that the country is going through. The study aims to identify the degree of environmental awareness about solid waste management in the area The study also clarifies the most important land routes that suffer from pollution with solid waste. The research was applied to a sample of the region’s population, which numbered 134 individuals. The study also sheds light on the most prominent effects resulting from it and the reasons that led to its spread. The severity of this phenomenon, and the study concluded that the lack of environmental awareness among community members and the absence of a sense of personal responsibility towards the cleanliness of their environment resulted in a low level of general hygiene, which led to the spread of solid waste and its accumulation on the edge of roads, streets, squares and forests in the study area. The study recommends working to spread awareness Citizens need to preserve the environment and work to provide specialized containers to encourage citizens to sort from the source This is in order to take advantage of the materials that can be recycled and to set a schedule that includes the arrival times of the compactor trucks designated for transporting waste and adhere to them.
Keywords: Solid Waste, Pollution, Road Network, Green Mountain Region, Environmental Geography